1897 Minn. Gen. Laws 229 - (:unkn) unknown (My University, 1897)
Ch. 118, pt. 3, art. 5, § 107: It shall not be lawful for any body of men whatever, other than the regularly organized national guard of this state, and the troops of the United States, to associate themselves together as a military company or organization, to drill or parade with arms in any city or town of this state, except the regular organization known as the Sons of Veterans
Keywords: MILITIAS